Assessment of time resolution impact on the modeling of a hybrid CSP-PV plant: A case of study in Chile. (15th May 2020) - Zurita, Adriana; Mata-Torres, Carlos; Cardemil, José M.; Escobar, Rodrigo A.
Highlights: CSP plant performance was the most affected by the time resolution. Control procedures were more realistically captured with 1–5 min time steps. A low time resolution leads to an information lost of variability effects. 5–60-minute data leads to an overestimation of 2–6% in the annual totals. Balance between accuracy and computational time is critical to select a time step. Abstract: This study analyzes the time resolution impact on the modeling of a hybrid CSP-PV plant integrated with thermal storage and a battery bank for two locations in Chile. Daily and annual results were evaluated varying the time resolution from 1, 5, 10, 15, 30 to 60 min, as well as the capacity factor and LCOE. In this way, the CSP plant was the component most affected by the time resolution, followed by the battery dispatch, while the effect on PV production estimation was marginal. Control procedures of the receiver and power block were more realistically captured with time steps between 1 and 5 min, while with higher time steps, variability effects were neglected. Annual and techno-economic results indicate an overestimation of the total yearly production of the hybrid plant as the time step is increased, leading to an underestimation of the LCOE. Variations in the capacity factor and LCOE were around ±2–3% in both locations using the 5-minute time step (with respect to the 1-min results), and between ±4–6% using 10–60 min time steps. Different cases of study varying the dispatch strategy and components sizing were evaluated, showing that time resolution impact is lower for oversized PV configurations with respect to the CSP plant, and higher when the CSP plant is oversized with respect to the PV, regardless the dispatch strategy. Finally, this work provides some recommendations analyzing the advantages and drawbacks of implementing different time steps at each stage in the development of a hybrid solar power plant.